Associations Between Eczema and Attention Deficit Hyperactivity Disorder Symptoms in Children - Loo, Evelyn Xiu Ling; Ooi, Delicia Shu Qin; Ong, Minyee; Ta, Le Duc Huy; Lau, Hui Xing; Tay, Michelle Jia Yu; Yap, Qai Ven; Chan, Yiong Huak; Tham, Elizabeth Huiwen; Goh, Anne Eng Neo; Van Bever, Hugo; Teoh, Oon Hoe; et al. (Frontiers in Pediatrics, 2022)
Background Epidemiological studies suggest a link between eczema and attention deficit hyperactivity disorder (ADHD), but underlying mechanisms have not been examined. Objective We aim to investigate the association between eczema and subsequent ADHD symptoms in the Growing Up in Singapore Towards healthy Outcomes cohort and explore the role of pro-inflammatory cytokines and gut microbiome. Methods The modified International Study of Asthma and Allergies in Childhood questionnaire and Computerized Diagnostic Interview Schedule for Children Version IV were administered to assess reported eczema within the first 18 months and presence of ADHD symptoms at 54 months, respectively. Skin prick testing at 18 months, cytokines in maternal blood during pregnancy and cord blood and the mediating role of the gut microbiome at 24 months were assessed. Results After adjusting for confounders, eczema with or without a positive skin prick test was associated with doubling the risk of ADHD symptoms. No differences in maternal and cord blood cytokines were observed in children with and without eczema, or children with and without ADHD. Gut microbiome dysbiosis was observed in children with eczema and children with ADHD. Children with eczema also had lower gut bacterial Shannon diversity. However, the relationship between eczema and ADHD was not mediated by gut microbiome. Conclusion Early life eczema diagnosis is associated with a higher risk of subsequent ADHD symptoms in children. We found no evidence for underlying inflammatory mechanism or mediation by gut microbiome dysbiosis. Further research should evaluate other mechanisms underlying the link between eczema and ADHD. Clinical Trial Registration [https://clinicaltrials.gov/ct2/show/NCT01174875], identifier [NCT01174875].